The Effect of Dividend Policy on Stock Price: Evidence from the Indian Market. (March 2019) - Singh, Narinder Pal; Tandon, Aakarsh
One of the most debated issue in the field of corporate finance is the relationship between dividend policy and market price of share. There is good amount of literature for and against this issue. The present study has been undertaken to evaluate the effect of dividend policy on market prices of shares of Nifty 50 companies listed on the National Stock Exchange (NSE) for 2008–2017. The data have been analysed by employing multiple panel data regression models namely pooled regression, fixed effect model and random effect model. The Hausman test has been used to suggest the most appropriate regression model. The result of the Hausman test indicates that random effect model is more relevant in describing the relationship among the given variables. The results of the random effect regression model support the relevant approaches of dividend policy. Thus, we conclude that there is significant effect of dividend policy on the stock price of firms.